Consort partner preference in male Tibetan macaques: How to choose when females conceal their ovulation? - Qi-Xin Zhang (Elsevier, 2021)
Growing evidence suggested that males suffer energetic costs from sexual behavior, males should discriminate among receptive females due to their reproductive quality, and deservedly, they would prefer females during the fertile phase. However, in species with females concealing their ovulation, males cannot identify the females’ fertile phase, and then what are the criteria for males to select their female partners? To answer this question, we collected behavioral data spanning two consecutive years (from February 2017 to January 2019) to investigate the effects of female individual, social and sexual traits on male consort partner choice in Tibetan macaques (Macaca thibetana), a species characterized by distinct seasonal breeding and female concealed ovulation, at Mt. Huangshan, China. Results showed that, in terms of individual traits, males prefer to consort with young/middle-aged, but not old or high-fecundity females; in terms of social traits, males did not engage in more consortship with high-ranking females or their previous non-sexual “friends”; in terms of sexual traits, males were more likely to consort with lower-polyandry females (the level of diversity of the female sexual solicitation). Besides, our results also showed that, compared to other males, alpha males consort more with higher-ranking and lower-polyandry females. Our study suggested that males selected their consort partner based on female sexual traits rather than individual and social traits. Contrary to the previous insights of sexual selection that emphasized female choice and male-male competition, the current study focused on male consort partner choice to provide new insights into the co-evolution of female concealed ovulation and male mating decisions.